Dynamics of ASEAN as Regional Organization in Resolving Human Security Issues in Southeast Asia - Hakim, Siti; Yusnaldi; Uksan, Arifuddin; Setiawibawa, Rachmat (Cita konsultindo, 2026)
This study examines the dynamics of ASEAN as a regional organization in the context of the shifting security paradigm from traditional state-centric security to non-traditional human security, with a specific focus on natural disaster management. Southeast Asia is highly vulnerable to massive, cross-border natural disasters that often overwhelm national capacities. However, the prevailing